Concomitant use of multiple antipsychotics to treat Schizophrenia: Risk benefit analysis - Tabassum, Fariha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022